2020
DOI: 10.1111/1541-4337.12645
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on the application of UV‐LED technology for microbial inactivation: Progress and mechanism

Abstract: Conventional technologies for the inactivation of microorganisms in food products have their limitations, especially changes in quality attributes that have led to quality deterioration, low consumer acceptance, impact on the environment, and potential health hazards (carcinogens). Ultraviolet (UV) light is an emerging promising nonthermal technology employed for microbial inactivation in water, liquid, and solid food products to curtail the limitations above. This review provides an insight into UV light-emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 128 publications
(205 reference statements)
0
67
0
Order By: Relevance
“…Unlike earlier UV devices with less than a 100-h lifespan (L50, 50% of light bulbs fail at 100 h), current UV-LEDs emitting at 280-310 nm now boast a lifespan of at least 3,000 h (Würtele et al, 2011;Fujioka et al, 2014;Kneissl, 2016), with some exceeding more than 10,000 h (Glaab et al, 2015). Although these UV-LEDs still have lower reliability and longevity than LEDs in visible spectrum, they have become an emerging radiation source for research involving UV germicidal irradiation, such as water treatment and microbial inactivation (Song et al, 2016;Kebbi et al, 2020).…”
Section: Uv Radiation and Photobiological Safetymentioning
confidence: 99%
“…Unlike earlier UV devices with less than a 100-h lifespan (L50, 50% of light bulbs fail at 100 h), current UV-LEDs emitting at 280-310 nm now boast a lifespan of at least 3,000 h (Würtele et al, 2011;Fujioka et al, 2014;Kneissl, 2016), with some exceeding more than 10,000 h (Glaab et al, 2015). Although these UV-LEDs still have lower reliability and longevity than LEDs in visible spectrum, they have become an emerging radiation source for research involving UV germicidal irradiation, such as water treatment and microbial inactivation (Song et al, 2016;Kebbi et al, 2020).…”
Section: Uv Radiation and Photobiological Safetymentioning
confidence: 99%
“…While UVB LEDs in particular (Kusuma et al, 2020) and UV lighting technologies in general are much less energy efficient than modern horticultural PAR fixtures (Nelson and Bugbee, 2014;Radetsky, 2018), UV fluence rates are also typically many times lower than the PAR spectrum. The functional lifespans of UVB LEDs are currently much lower (Kebbi et al, 2020) than common horticultural LEDs (Kusuma et al, 2020); potentially leading to relatively rapid degradation in fluence rates over time. Given that plant responses in the present study were closely tied to the UV exposure level, fixture degradation could lead to inconsistencies between sequential crops, which is an important parameter in the indoor cannabis production industry.…”
Section: Implications For Uv Use In Indoor Cannabis Production and Future Research Directionsmentioning
confidence: 99%
“…It has also been shown that some microorganisms can recover from sub-lethal UVirradiation through a photoenzymatic process called photoreactivation [28]. To overcome this issue, UV light is often used in combination with photocatalytic materials, also known to as photocatalysts [29,30], such that UV photocatalytic oxidation (PCO) has become the most exploited air sanitation technology [31][32][33].…”
Section: Introductionmentioning
confidence: 99%